Static and fatigue performance of steel bridge decks strengthened with air-cured UHPC. (July 2022) - Liu, Yiming; Zhang, Qinghua; Bu, Yizhi; Bao, Yi
Graphical abstract: Abstract: Adding a thin layer of ultra-high performance concrete (UHPC) onto the steel deck plate is an effective approach to improve the fatigue performance of orthotropic steel decks (OSDs) through increasing structural stiffness and load-carrying capacity, but a wide industrial acceptance of the approach is hindered by heat curing of UHPC. In this study, air-cured UHPC with low shrinkage was adopted to fabricate the cast-in-situ topping layer for the composite decks. Experiments were carried out to investigate the structural behavior of the composite decks under static and fatigue loading. Experimental results showed that (1) UHPC with relatively high strengths and low shrinkage could be manufactured without any special curing regime; and (2) the composite decks had enough mechanical strengths and fatigue resistance to withstand service loads. Finite element analyses were performed to determine the contribution of air-cured UHPC on the fatigue performance of OSDs. Finally, a hot spot stress reduction factor was introduced to assess the long-term effectiveness of air-cured UHPC in improving the fatigue performance of OSDs. Results suggested that UHPC cracking and the associated degradation in structural stiffness had limited effects on the fatigue behaviors of composite decks.